2017
DOI: 10.3847/1538-4365/228/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Candels Multi-Wavelength Catalogs: Source Identification and Photometry in the Candels Cosmos Survey Field

Abstract: We present a multi-wavelength photometric catalog in the COSMOS field as part of the observations by the Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey. The catalog is based on Hubble Space Telescope Wide Field Camera 3 (HST/WFC3) and Advanced Camera for Surveys observations of the COSMOS field (centered at R.A.: 10 00 28 h m s , Decl.: +  ¢  02 12 21 ). The final catalog has 38671 sources with photometric data in 42 bands from UV to the infrared ( -m0.3 8 m). This includes broadband photom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 178 publications
(352 reference statements)
10
98
0
Order By: Relevance
“…K) band selection, as done in previous analyses. Deeper HST data available in the overlap with the CANDELS field (Nayyeri et al 2017) have been used to confirm the absence of significant biases in our final sample, cut at [3.6] < 25.…”
Section: Discussionmentioning
confidence: 99%
“…K) band selection, as done in previous analyses. Deeper HST data available in the overlap with the CANDELS field (Nayyeri et al 2017) have been used to confirm the absence of significant biases in our final sample, cut at [3.6] < 25.…”
Section: Discussionmentioning
confidence: 99%
“…Such systematics in the measurement of stellar mass introduces up to ∼ 0.5 dex offset in the number densities for the higher redshift bins. To further complicate the picture, recent works have shown that when the correction for nebular line contamination is applied on a statistical basis, irrespective of the specific SEDs, it can even boost the stellar mass measurements by up to ∼ 0.2 − 0.3 dex (Stefanon et al 2015;Stefanon 2017;Nayyeri et al 2017).…”
Section: Schechter Best-fit To the Lf And Smfmentioning
confidence: 99%
“…Similar to all the rest of the CANDELS fields (Guo et al 2013;Galametz et al 2013;G. Barro et al 2017, in preparation;Nayyeri et al 2017), object detection was performed on the WFC3/F160W-band image. This mosaic is fully covered by all the adopted data sets, with the exception of the data from the NMBS and the WFC3 F140W mosaic,which cover only about one-thirdand two-thirdsof the F160W field respectively (see Figure 2).…”
Section: Datamentioning
confidence: 99%
“…The CANDELS GOODS-S data, combined withthe medium bands from Subaru (Cardamone et al 2010), were also used in Hsu et al (2014) to compute photometric redshifts of normal galaxies and AGNs. The description of the multi-wavelength catalogs, photometric redshifts, and stellar population parameters for the COSMOS and GOODS-N fields are presented by Nayyeri et al (2017) and G. Barro et al (2017, in preparation), respectively. This paper presents the CANDELS multi-wavelength photometric catalog for the EGS field.…”
Section: Introductionmentioning
confidence: 99%